2006
DOI: 10.1016/j.plantsci.2006.06.008
|View full text |Cite
|
Sign up to set email alerts
|

RETRACTED: The antifungal properties of a 2S albumin-homologous protein from passion fruit seeds involve plasma membrane permeabilization and ultrastructural alterations in yeast cells

Abstract: This article has been retracted at the request of the Publisher. The Publisher regrets that this article was an accidental publication of an article that has already been published in Plant Science, 171 (4), page 515-522, doi:10.1016/j.plantsci.2006.06.001. The duplicate article has therefore been withdrawn from Plant Science, 171 (2006) pages 523-530.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…TEM imaging showed the accumulation of silver particles due to silver exposure and abnormal intracellular appearances. Similar results exist for S. cerevisiae exposed to 2 mM AgNO 3 and the allergen 2S albumin [ 37 , 42 ]. Overall, TEM results indicated that NS commercial yeast had the capability to produce AgNPs after transient AgNO 3 exposure, even at a level of silver exposure that is detrimental to cellular growth, demonstrating S. cerevisiae suitability for AgNPs mycosynthesis.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…TEM imaging showed the accumulation of silver particles due to silver exposure and abnormal intracellular appearances. Similar results exist for S. cerevisiae exposed to 2 mM AgNO 3 and the allergen 2S albumin [ 37 , 42 ]. Overall, TEM results indicated that NS commercial yeast had the capability to produce AgNPs after transient AgNO 3 exposure, even at a level of silver exposure that is detrimental to cellular growth, demonstrating S. cerevisiae suitability for AgNPs mycosynthesis.…”
Section: Discussionsupporting
confidence: 75%
“…The analysis produced results for NS commercial yeast; however, results for NS naïve yeast were inconclusive. Figure 6 a shows micrographs for NS commercial yeast unexposed to AgNO 3 ; typical morphology was observed, with no visible accumulation of any particles [ 37 , 38 ]. The corresponding energy-dispersive X-ray spectroscopy (EDS) spectrum showed no intracellular silver accumulation ( Figure 6 (a1)).…”
Section: Resultsmentioning
confidence: 99%
“…The result revealed that Mo-CBP 3 is a member of the 2S albumin family. Based on previous literature by [109,110], various biological activity is associated with 2S albumins, including antifungal properties it poses in barley and passion fruit.…”
Section: Antifungal Action Of Moringa Oleiferamentioning
confidence: 99%